Local setup reproducibility of the spinal column when using intensity-modulated radiation therapy for craniospinal irradiation with patient in supine position - Stoiber, Eva Maria; Giske, Kristina; Schubert, Kai; Sterzing, Florian; Habl, Gregor; Uhl, Matthias; Herfarth, Klaus; Bendl, Rolf; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2011)
Purpose - To evaluate local positioning errors of the lumbar spine during fractionated intensity-modulated radiotherapy of patients treated with craniospinal irradiation and to assess the impact of rotational error correction on these uncertainties for one patient setup correction strategy. - Methods and Materials - 8 patients (6 adults, 2 children) treated with helical tomotherapy for craniospinal irradiation were retrospectively chosen for this analysis. Patients were immobilized with a deep-drawn Aquaplast head mask. Additionally to daily megavoltage control computed tomography scans of the skull, once-a-week positioning of the lumbar spine was assessed. Therefore, patient setup was corrected by a target point correction, derived from a registration of the patient's skull. The residual positioning variations of the lumbar spine were evaluated applying a rigid-registration algorithm. The impact of different rotational error corrections was simulated. - Results - After target point correction, residual local positioning errors of the lumbar spine varied considerably. Craniocaudal axis rotational error correction did not improve or deteriorate these translational errors, whereas simulation of a rotational error correction of the right-left and anterior-posterior axis increased these errors by a factor of 2 to 3. - Conclusion - The patient fixation used allows for deformations between the patient's skull and spine. Therefore, for the setup correction strategy evaluated in this study, generous margins for the lumbar spinal target volume are needed to prevent a local geographic miss. With any applied correction strategy, it needs to be evaluated whether or not a rotational error correction is beneficial.